PENGARUH PENAMBAHAN GARAM DAN ES TERHADAP KARAKTERISTIK ORGANOLEPTIK IKAN LEMURU DAN IKAN GABUS ASAL NUSA TENGGARA BARAT: The Effect of Salt and Ice Addition on the Organoleptic Characteristics of Lemuru and Snakehead Fish from West Nusa Tenggara - Nufus, Chairun (Yayasan Al-Amin Qalbu, 2025)
Keeping fish in a fresh condition is very important. The use of ice and the addition of salt to maintain fish freshness are the most commonly used techniques for preserving fish. This study aims to determine the effect of adding salt and ice on the organoleptic and hedonic characteristics of lemuru fish (Sardinella lemuru) and snakehead fish (Channa striata). The research used an experimental method with four treatments and three replications, using a salt concentration of 10%. The ice-to-fish ratio was 1:1, with a storage duration of 24 hours. The results showed that the organoleptic test scores for fresh fish ranged from 6 to 9, and for boiled fish ranged from 4 to 9, indicating that the fish was still in a fresh condition. Meanwhile, the hedonic test results for fresh and boiled fish ranged from 2 to 8, with categories ranging from